The concept "personality" in book "The Beauty of the Infinite" of David Hart - Kostiantyn Bublyk (Cхід, 2016)
The article critically analyzes concept of "personality" in Orthodox theology of American thinkers D.B.Hart. Personology of D.B.Hart present the contours of Orthodox postmodern theology. Orthodox thought in its historical development has experienced a significant influence metaphysical philosophy and remained until recently. Anti-metaphysical turn in Orthodox theology and religious philosophy associated with the use of phenomenology and hermeneutics in the project "theological aesthetics" by David Bentley Hart and John Panleymona Manoussakis. These American Orthodox theologians were really able to create a new type of Orthodox thought, post-metaphysical in nature. As an Orthodox theologian, D.B.Hart rejects the thesis of the inability of Orthodox thought formalize its position except in opposition to Roman Catholic theology. He accepts the doctrine of the person as a special relationship of Augustine and modern Roman Catholic theologians.